Managing Anaemia in Pregnancy with Traditional Medicines: Experiences of women in the Cape Coast Metropolis, Ghana - Theodora Dedo Azu; Margaret Nyarko-Sampson; Esther Danquah; Patience Fakornam Doe (PLoS ONE, 2026)
Anaemia in pregnancy (AIP) is diagnosed when a pregnant woman’s haemoglobin levels fall below 11g/dL. Globally, traditional medicines (TM) are widely used in the management of pregnancy-related conditions. This study aims to explore the experiences and management practices associated with the use of TMs to manage AIP. Materials and methods A qualitative exploratory descriptive design was used to explore the experiences of pregnant women. Semi-structured face-to-face interviews were conducted among 18 pregnant women during their antenatal visits. Interviews were audio-recorded and transcribed verbatim for analysis. The researchers developed a codebook and used NVIVO 12 to analyse the transcribed data, Results and analysis The women and their partners had lower socio-economic status (education, occupation and monthly income). The women selected for the study knew about the causes of AIP, including poor medication adherence and their inability to eat well. The women used TMs to manage AIP; however, they were concerned about the side effects on themselves and their fetuses. Although health workers discouraged the women from using TMs, family, friends, and communities encouraged their use. Conclusion The women in this study perceived that traditional medicines could help manage AIPs, although they also reported concerns about adverse effects following use. Given the widespread accessibility of these remedies, further research is needed to clarify their safety, potential benefits, and appropriate use. Rather than outright discouragement, efforts should focus on strengthening supervised care and referral pathways.